Molecular systematics of sturgeon nucleocytoplasmic large DNA viruses - Clouthier, Sharon; Anderson, Eric; Kurath, Gael; Breyta, Rachel (Molecular phylogenetics and evolution, 2018)
DNA polymerase B elongation subunit. [Display omitted] •NV is a member of the Mimiviridae family and shares a common ancestor with CroV.•Sturgeon NCLDV form a cohesive monophyletic group comprised of four lineages.•Congruent evolutionary relationships for NV were obtained with 9 orthologous proteins.•Stable tree topologies with datasets differing in sequence, sequence length and taxa.•NV sequence dataset encodes orthologues of Mimivirus-specific proteins. Namao virus (NV) is a sturgeon nucleocytoplasmic large DNA virus (sNCLDV) that can cause a lethal disease of the integumentary system in lake sturgeon Acipenser fulvescens. As a group, the sNCLDV have not been assigned to any currently recognized taxonomic family of viruses. In this study, a data set of NV DNA sequences was generated and assembled as two non-overlapping contigs of 306,448 bp and then used to conduct a comprehensive systematics analysis using Bayesian inference of phylogeny for NV, other sNCLDV and representative members of six families of the NCLDV superfamily. The phylogeny of NV was reconstructed using protein homologues encoded by nine nucleocytoplasmic virus orthologous genes (NCVOGs): NCVOG0022 – mcp, NCVOG0038 – DNA polymerase B elongation subunit, NCVOG0076 – VV A18-type helicase, NCVOG0249 – VV A32-type ATPase, NCVOG0262 – AL2 VLTF3-like transcription factor, NCVOG0271 – RNA polymerase II subunit II, NCVOG0274 – RNA polymerase II subunit I, NCVOG0276 – ribonucleotide reductase small subunit and NCVOG1117 – mRNA capping enzyme. The accuracy of our phylogenetic method was evaluated using a combination of Bayesian statistical analysis and congruence analysis. Stable tree topologies were obtained with data sets differing in target molecule(s), sequence length and taxa. Congruent topologies were obtained in phylogenies constructed using individual protein data sets. The major capsid protein phylogeny inferred that ten representative sNCLDV form a monophyletic group comprised of four lineages within a polyphyletic Mimi-Phycodnaviridae group of taxa. Overall, the analyses revealed that Namao virus is a member of the Mimiviridae family with strong and consistent support for a clade containing NV and CroV as sister taxa.